cAMP analogues downregulate the expression of granulocyte macrophage colony-stimulating factor (GM-CSF) in human bone marrow stromal cells in vitro - G. Bug; J. Aman; C. Huber; C. Peschel; H. G. Derigs (Mediators of Inflammation)
The stimulation of granulocyte macrophage-colony stimulating factor (GM-CSF) by interleukin-1 (IL-1) has been shown to be counteracted in different mesenchymal cell systems by cyclic adenosine monophosphate (cAMP) agonists. The aim of this study was the evaluation of different cAMP agonists on GM-CSF expression in human bone marrow stromal cells. Incubation of secondary haematopoietic progenitor cell deprived human stromal cell cultures with IL-1 or TNF- α induced GM-CSF protein expression in culture supernatants and GM-CSFmRNA in adherent stromal cells. The coincubation with 8-bromo-cAMP (8BrcAMP), a water soluble cAMP analogue, inhibited this GM-CSF stimulation at the protein and the m RNA level. This effect was dose dependent with a maximal inhibition of about 65% occurring at a 8BrcAMP concentration of 0.75 mM. In addition to 8BrcAMP, other cAMP agonists such as dibutyryl-cAMP, forskolin, pertussis toxin, or prostaglandin E2 (PGE2) had the same inhibitory effect on GM-CSF stimulation by IL-1. Coincubation with the cyclooxygenase inhibitor indomethacin had no significant influence on GM-CSF expression in stromal cells. Our results provide evidence that the previously described inhibitory effect of cAMP agonist PGE2 on haematopoietic progenitor cells in vivo is, at least in part, mediated by modulating the expression of GMCSF in bone marrow stromal cells.